BUILD WEB BUMI INDAH RAYA USING PHP - Noor Wiyanto; Don Elsyafitra, SKom Don Elsyafitra, SKom (Jurnal Sistem Informasi, 2004)
The Internet is the development of the information on the world of information at thistime. information may be presented through the web. PT. Bumi Indah Raya inincreasing sales to attract customers as much as possible, then be made to the web asa means of promotion were deemed most effective with an economical cost withPHP.